Islam Nusantara in Political Contestation Identity Religion in Indonesia - Khamdan, Moh.; Wiharyani, W (LPPM IAIN Kudus, 2018)
The relationship between the religion represented by Islam and the State that is represented by the democratic political system continues remain to be a problem. Ideological debates that Islamic law should be implemented and escorted through Islamic countries experiencing resistance against groups who argued that Islam is a substance that is in compliance with democracy. Religious ideology has often been a motivation to justify the struggle through the violence that has been done. Strengthening of violence in the name of religion is regarded as a form of struggle for bottomic beliefs and religious form in kaffah. Nationalism of Islamic religion Leaders by receiving Pancasila as the Indonesian ideology its been a moderate wisdom that has taken to maintain the unity of Indonesia, while keeping the existence of religions living. The relationship of religion and the State by Islamic religion Leaders of Nahdhatul Ulama (NU) considered as a mutual-connection with maintaining Indonesian nationalism without discriminating treatment of religions, tribes, and inter-group relations is face Islam Nusantara in Indonesia. Politics as the source of radicalism muted by NU leaders with a fatwa that receiving of Pancasila both as the nations foundation and as a spirit of Islam Nusantara. This research uses psychology politics theory and the theory of social identity’s approach that analyzing potential radicalism in society.